Functional divergence in the genus Oenococcus as predicted by genome sequencing of the newly-described species, Oenococcus kitaharae. - Anthony R Borneman (Public Library of Science (PLoS), 2012)
Oenococcus kitaharae is only the second member of the genus Oenococcus to be identified and is the closest relative of the industrially important wine bacterium Oenococcus oeni. To provide insight into this new species, the genome of the type strain of O. kitaharae, DSM 17330, was sequenced. Comparison of the sequenced genomes of both species show that the genome of O. kitaharae DSM 17330 contains many genes with predicted functions in cellular defence (bacteriocins, antimicrobials, restriction-modification systems and a CRISPR locus) which are lacking in O. oeni. The two genomes also appear to differentially encode several metabolic pathways associated with amino acid biosynthesis and carbohydrate utilization and which have direct phenotypic consequences. This would indicate that the two species have evolved different survival techniques to suit their particular environmental niches. O. oeni has adapted to survive in the harsh, but predictable, environment of wine that provides very few competitive species. However O. kitaharae appears to have adapted to a growth environment in which biological competition provides a significant selective pressure by accumulating biological defence molecules, such as bacteriocins and restriction-modification systems, throughout its genome.